THE CONTINUITY OF AMRUS NATALSYA’S POPULIST PARADIGM, ICONOGRAPHY-ICONOLOGY REVIEW OF “TANAH AIRKU” (2013) PAINTING - Miftahul Khairi (LPPMPP Institut Seni Indonesia Padangpanjang, 2019)
This study analyzes the Amrus Natalsya’s painting entitled